Decomposing changes in the aggregate labor force participation rate - Julie L. Hotchkiss (Federal Reserve Bank of Atlanta, 2009)
This paper presents a simple methodology for decomposing changes in the aggregate labor force participation rate (LFPR) over time into demographic group changes in labor force participation behavior and in population share. The purpose is to identify the relative importance of behavioral changes and population changes as driving forces behind changes in the aggregate LFPR.
Keywords: J11; J21; E24; 330; labor force participation; decomposition; forecasting